Perlindungan Hak Upah Bagi Pekerja Dalam Lingkup Usaha Mikro Kecil Menengah - Alexander Kennedy (Fakultas Hukum, Universitas Warmadewa, 2024)
Wage protection for workers in the Micro, Small, and Medium Enterprises (MSME) sector is a crucial element in creating social and economic balance in Indonesia. Although MSMEs significantly contribute to the economy by absorbing nearly 97% of the workforce, many workers still face inadequate wages. This issue stems from factors such as financial limitations and a lack of understanding of labor regulations. This study aims to analyze the mechanism of wage protection in MSMEs and the role of legal culture in preventing violations of workers' rights. Using a normative juridical approach, the study examines relevant legal documents, including Government Regulation Number 36 of 2021 on Wages. The main findings show that existing regulations have not fully ensured the fulfillment of workers' wage rights, particularly in regions with less effective oversight. Additionally, the legal culture among MSME business owners and workers influences the implementation of these regulations. The results highlight the importance of an integrated approach between the government, business owners, and workers to ensure effective wage protection and social justice.